Memotret Tipologi Tasawuf Kontemporer: Capturing the Typology of Contemporary Sufism - Mahjuddin Mahjuddin (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2017)
The phenomenon of contemporary Sufism emerges as a response to the inability of modern sociology and materialistic progress to provide spiritual peace, often neglecting metaphysical reality and social morality. This article aims to examine the typology, basic doctrines, and social applications of contemporary Sufism, distinguishing it from classical Sufism. Using a library research approach with descriptive-analytical method, the study explores various perspectives from figures such as Fazlur Rahman, Ahmad Najib Burhani, and Sudirman Tebba. The findings show that contemporary Sufism integrates individual piety (through dhikr and sunnah practices) with social piety (through infaq, zakat, and concern for society and the environment). It rejects extreme asceticism and fatalism, promoting engagement with economy, governance, law, education, and mental health. The study concludes that contemporary Sufism offers a balanced spiritual-social model, with recommendations to apply its doctrines in daily life for inner happiness and communal well-being. Fenomena tasawuf kontemporer muncul sebagai respons terhadap ketidakmampuan sosiologi modern dan kemajuan materialistik dalam memberikan ketenteraman spiritual, yang sering mengabaikan realitas metafisik dan moral sosial. Artikel ini bertujuan mengkaji tipologi, doktrin dasar, dan penerapan sosial tasawuf kontemporer, serta membedakannya dengan tasawuf klasik. Dengan metode penelitian kepustakaan dan pendekatan deskriptif-analitis, studi ini mengeksplorasi berbagai perspektif dari tokoh seperti Fazlur Rahman, Ahmad Najib Burhani, dan Sudirman Tebba. Hasil penelitian menunjukkan bahwa tasawuf kontemporer mengintegrasikan kesalehan individual (melalui zikir dan amalan sunah) dengan kesalehan sosial (melalui infak, zakat, dan kepedulian pada masyarakat serta lingkungan). Tasawuf ini menolak asketisme ekstrem dan fatalisme, serta mendorong keterlibatan dalam ekonomi, pemerintahan, hukum, pendidikan, dan kesehatan mental. Kesimpulannya, tasawuf kontemporer menawarkan model spiritual-sosial yang seimbang, dengan rekomendasi untuk mengamalkan doktrinnya dalam kehidupan sehari-hari demi kebahagiaan batin dan kesejahteraan bersama.